Sosialisasi dan Pelatihan Pengolahan Jamur Tiram bagi Kelompok Tani Hutan (KTH) Tunas Berkah Desa Jatimulya Kec. Wonosari Kab. Boalemo - Satria Wati Pade; Deyvie Xyzquolyna; Minarni Tolapa2 (Sam Ratulangi University, 2023)
The service partner, namely KTH Tunas Berkah, has several problems from year to year, namely the lack of education about the health benefits of oyster mushrooms and the lack of variations in processed oyster mushrooms. Based on these problems, partners were offered several solutions, namely socialization and counseling about product knowledge and the introduction of easy and preferred processing of processed products. This service activity involves 2 students as an off-campus learning process which is equivalent to 5 credits. Student activities will be monitored and evaluated based on the output produced by students. As for Partners, the proposing team will conduct regular monitoring and evaluation to ensure the sustainability of technology adoption developed by partners. In the socialization and counseling activities, the benefits of oyster mushrooms for the health of the human body were conveyed. In product processing training activities, partners provide an alternative to processing oyster mushrooms into processed products of economic value with low production costs, namely by processing oyster mushrooms into frozen food in the form of nuggets and crackers. Keywords: Oyster mushroom; Nugget; Crackers; KTH ABSTRAK Mitra pengabdian yaitu KTH Tunas Berkah memiliki beberapa permasalahan dari tahun ke tahun yaitu kurangnya edukatif tentang manfaat kesehatan jamur tiram serta minimnya variasi olahan jamur tiram. Berdasarkan pemaslahan tersebut, mitra ditawari beberapa solusi yaitu sosialisasi dan penyuluhan tentang product knowledge dan introduksi pengolahan produk olahan yang mudah dan disukai. Kegiatan pengabdian ini melibatkan mahasiswa sebanyak 2 orang sebagai proses pembelajaran di luar kampus yang setara dengan 5 SKS. Kegiatan mahasiswa akan dimonitoring dan evaluasi berdasarkan output yang dihasilkan oleh mahasiswa. Sedangkan untuk Mitra, tim pengusul akan melakukan monitoring dan evaluasi secara berkala untuk memastikan keberlanjutan adopsi teknologi yang dikembangkan oleh mitra. Pada kegiatan soialisasi dan penyuluhan disampaikan mengenai manfaat jamur tiram untuk kesehatan tubuh manusia. Pada kegiatn pelatihan pengolahan produk, mitra memberikan alternatif pengolahan jamur tiram menjadi produk olahan bernilai ekonomis dengan biaya produksi rendah yaitu dengan mengolah jamur tiram menjadi frozen food yaitu berupa nugget dan kerupuk. Kata Kunci: Jamur tiram; Nugget; Kerupuk; KTH;